Teaching presence predicts cognitive presence in blended learning during COVID-19: The chain mediating role of social presence and sense of community - Li, Ling (Frontiers in Psychology, 2022)
With the continuous lockdown and staying home strategies of COVID-19, both instructors and learners have met with presence challenges in language learning. To address the complex and dynamic relationships of different presences in blended learning during COVID-19, based on the Community of Inquiry framework, 215 Chinese English learners were obtained as samples for an empirical test. SPSS 23 and PROCESS for SPSS were utilized to examine the hypotheses. Results indicate that teaching presence (TP) has a significant direct positive impact on social presence (SP), sense of community (SoC) and cognitive presence (CP). SP has a significant positive impact on CP and partially mediates the relationship between TP and CP. SoC is also found to impact CP and partially mediates the relationship between TP and CP. The findings also validate the chain mediating role of SP and SoC between TP and CP. Pedagogical implications are discussed.